2019
DOI: 10.1021/acs.chemmater.9b04275
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Mineralizing Microenvironments Generated by Liquid–Liquid Phase Coexistence

Abstract: Living organisms direct the location, structure, and properties of biominerals by tightly controlling reactant concentration profiles, biopolymer identity and availability, and other aspects of reaction microenvironments. Such control at the microscale is difficult to exert in synthetic systems. Inspired by the scalability of emulsions and the effectiveness of liquid−liquid phase separation in organizing subcellular biochemistry, we introduce mineralizing microreactors based on vesicle-coated multiphase drople… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Second, the process of delivery and flow through the extracellular environment is further facilitated by the low interfacial energy of coacervate microdroplets with the dilute phase , as well as by their shear-thinning rheological characteristics. , Third, microdroplets can recruit both inorganic ions as well as larger macromolecules to compartmentalize, protect, and/or enhance localized chemical activity. For example, protein microdroplets can recruit inorganic ions such as Ca 2+ , CO 3 2– , and PO 4 3– and stabilize intermediate phases, thereby delaying premature precipitation which is important during biomineralization. In other cases, compartmentalization within the droplet is beneficial to regulate or delay chemical reactivity, such as oxidation of dihydroxylphenylalanine (Dopa) in mussel adhesive proteins , or in sandcastle worm glue, in turn allowing the organism to spatiotemporally control the chemical reactions required to form the final matured structure.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the process of delivery and flow through the extracellular environment is further facilitated by the low interfacial energy of coacervate microdroplets with the dilute phase , as well as by their shear-thinning rheological characteristics. , Third, microdroplets can recruit both inorganic ions as well as larger macromolecules to compartmentalize, protect, and/or enhance localized chemical activity. For example, protein microdroplets can recruit inorganic ions such as Ca 2+ , CO 3 2– , and PO 4 3– and stabilize intermediate phases, thereby delaying premature precipitation which is important during biomineralization. In other cases, compartmentalization within the droplet is beneficial to regulate or delay chemical reactivity, such as oxidation of dihydroxylphenylalanine (Dopa) in mussel adhesive proteins , or in sandcastle worm glue, in turn allowing the organism to spatiotemporally control the chemical reactions required to form the final matured structure.…”
Section: Introductionmentioning
confidence: 99%
“…These studies consistently demonstrated that confinement already strongly impacts the crystallization kinetics and CaCO 3 polymorphism. To assess the influence of a lipidic interface on CaCO 3 mineralization in confined space, Keating and co-workers , used aqueous emulsion droplets stabilized by lipid vesicles. However, these systems do not resemble a continuous lipid bilayer like it is found in biomineral-forming vesicles in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Dense polymer–Ca 2+ phases, or coacervates, have been suggested to be functional precursors in the formation of Ca-based minerals. ,, The unique aspect of a mechanism involving polymer–Ca 2+ phases in comparison to other multistep pathways is that it separates temporally the precipitation of the cations from the addition of the anions. , Such a step-by-step mechanism can be advantageous in biomineralization processes, where calcium carbonate minerals form within the Ca 2+ -poor environment of the cell. Our results provide mechanistic insights into such processes, demonstrating how functional polymers can scavenge Ca 2+ from solutions with concentrations in the submillimolar range.…”
Section: Discussionmentioning
confidence: 99%
“…This dense CAP-Ca 2+ phase was shown to form in the absence of carbonate ions. , Nevertheless, if carbonate ions are added to the dense CAP-Ca 2+ phase after its formation, it transforms into a calcium carbonate phase that ultimately converts into calcite . These observations might be an indication that a dense polymer–ion complex, or coacervate, is a functional precursor phase to mineral formation. The dynamics of the CAP-Ca 2+ dense phase formation, however, have not been explored, and we have yet to understand the chemical conditions and interactions controlling this precipitation process.…”
Section: Introductionmentioning
confidence: 99%